Kontekstualisasi Gerakan Lingkungan melalui Pendidikan Alternatif pada Pesantren Agroekologi BhU di Kabupaten Bogor - Adawiah, Wardatul; Fauzi, Agus Machfud; Syaifullah, Khalid (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2025)
This study examines the role of Pondok Pesantren Agroecology BhU in Bogor Regency as an alternative, environmentally based educational center responding to socio-ecological crises caused by the proliferation of gold mining activities. Employing a qualitative approach with an ethnographic method, the research traces the genealogy of the environmental movement and the critical pedagogical strategies implemented by the pesantren. The pesantren serves as a counter-discourse arena against the dominant knowledge regime that legitimizes extractive economies, fostering the structural awareness of students and the community while revitalizing agrarian practices and local ecological values. Findings reveal that critical education in the pesantren not only transfers knowledge but also cultivates ecological consciousness and social justice, linking Islamic spirituality with environmental advocacy. This model highlights the potential of pesantren as key actors in building socio-ecological resilience and resisting extractive capitalism, while offering a contextual educational framework relevant to vulnerable communities.